A prospective, randomized comparison of 3 types of proximal interphalangeal joint arthroplasty - Daecke, Wolfgang Heinz Manfred; Kaszap, Balázs; Martini, Abdul-Kader; Hagena, Frank-Wolfgang; Jung, Martin (The journal of hand surgery. [American volume], 2012)
Purpose For surface replacement arthroplasty in proximal interphalangeal joint osteoarthritis, titanium-polyethylene (TI) and pyrocarbon (PY) implants are frequently used. However, their superiority in comparison to the silicone (SI) spacer has not been established. The purpose of this study was to compare these 3 types of implants with regard to outcome. Methods A prospective, randomized, multicenter trial was performed. A total of 43 patients (62 proximal interphalangeal joints) had surgery in the 3 participating centers, and each patient was randomly allocated to one of the 3 groups (TI, PY, SI). Range of motion (ROM) and strength were measured before surgery; pain and disability self-assessment and radiographic analysis were also completed. The same examination protocol was planned for 3 months, 6 months, and 1, 2, and 3 years after surgery, but some follow-up visits did not take place due to patient death or poor compliance. Results The mean follow-up time at the ﬁnal follow-up was 35 Ϯ 3 months (range, 30 - 41 mo). All implant types led to signiﬁcant pain reduction at rest and at load. Tip pinch strength was slightly improved by all 3 devices at the 3-year follow-up. No signiﬁcant improvement in ROM for silicone or resurfacing implants was found. However, when comparing the highest ROM values reached after surgery, the resurfacing devices tended to show superior joint motility compared to silicone spacers, albeit only temporarily and not signiﬁcantly. Sixteen explantations were necessary: 2 of 18 SI (11%), 7 of 26 TI (27%) and 7 of 18 PY (39%) implants had to be removed. An additional 4 secondary surgical procedures were performed in group TI. Conclusions Surface replacement arthroplasty devices showed a tendency for a temporarily superior maximum postoperative ROM, but markedly higher postoperative complication and explantation rates were observed compared to the silicone spacer implantation. (J Hand Surg 2012;37A:1770-1779. Copyright © 2012 by the American Society for Surgery of the Hand. All rights reserved.)